1988
DOI: 10.1007/bf00254241
|View full text |Cite
|
Sign up to set email alerts
|

Report on nationwide pooled data and cohort investigation in UFT phase II study

Abstract: UFT is a compound in which futraful (FT) and uracil are combined at a ratio of 1:4. UFT was given orally at a daily dose of 300-600 mg in a phase II study. Pooled data on a UFT phase II study of 438 evaluable patients, at 104 institutions revealed a response in carcinoma of the stomach (27.7%), pancreas (25.0%), gallbladder and bile duct (25.0%), liver (19.2%), colon and rectum (25.0%), breast (32.0%), and lung (7.0%). The mainly gastrointestinal toxicity resulted in anorexia (24.3%), nausea and vomiting (12.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(71 citation statements)
references
References 5 publications
4
65
2
Order By: Relevance
“…Among 117 patients with insensitive tumors, 5-year survival rate was similar in the UFT group (68.1%) and the control group (76.6%) (P = 0.373) dicted to have UFT-sensitive tumors. This value is similar to the rate of tumor sensitivity to UFT in the phase II study of this drug (Ota et al 1988) and also the conventional treatment with 5-FU (loading or weekly bolus) in patients with metastatic colorectal cancer (Thirion et al 2004).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Among 117 patients with insensitive tumors, 5-year survival rate was similar in the UFT group (68.1%) and the control group (76.6%) (P = 0.373) dicted to have UFT-sensitive tumors. This value is similar to the rate of tumor sensitivity to UFT in the phase II study of this drug (Ota et al 1988) and also the conventional treatment with 5-FU (loading or weekly bolus) in patients with metastatic colorectal cancer (Thirion et al 2004).…”
Section: Discussionsupporting
confidence: 70%
“…A response rate of UFT for colorectal carcinoma is around 20% (Ota et al 1988). UFT is commonly used for an adjuvant setting for curatively resected colorectal carcinoma without any evidence, by large randomized controlled studies in Japan when we started conducting this trial in 1992.…”
Section: Discussionmentioning
confidence: 99%
“…7 Conversely, S-1 showed a 22% response rate for advanced NSCLC in a previous phase II trial, 8 raising the question of whether S-1 has sufficient power as adjuvant advanced NSCLC, uracil-tegafur, another oral fluoropyrimidine, could be administered long-term (2 years) and, thus, could allow administration of sufficient amounts to prevent recurrence or metastasis, because the drug has extremely low toxicity and is easily continued as an oral medication. 9 Although the exact mechanisms of action accounting for the efficacy of uracil-tegafur treatment in the postoperative adjuvant setting remain unclear, long-term 100 uracil-tegafur administration may inhibit the development of postoperative recurrence through antiangiogenic effects in addition to direct cytotoxic effects. 10 In terms of S-1-based adjuvant chemotherapy, in the field of gastric cancer, a feasibility study has already been performed and achieved a high completion rate of 60% and a favorable drug compliance rate of 70%.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier preclinical studies have demonstrated that it can inhibit tumour growth and prolong patients' lives through inhibition of tumour neovascularisation (Maehara et al, 1988;Ota et al, 1988).…”
mentioning
confidence: 99%